The Effect of Price, Promotion, and Brand Image on Mixue Repurchase Interest in Garut Regency - Rizki Firdaus; Hariyadi Triwahyu Putra (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to examine the effect of price, promotion, and brand image on consumers’ repurchase intention of Mixue products in Garut Regency. This research employs a quantitative approach using primary data collected through a structured questionnaire distributed to 120 respondents who have purchased Mixue products. Respondents were selected using a convenience sampling method to ensure accessibility and relevance. The research instrument was tested for validity and reliability, and both were confirmed to meet statistical standards. Data analysis was conducted using SPSS Statistics version 27, applying multiple linear regression to test the hypotheses. The results indicate that price, promotion, and brand image each have a positive and significant impact on repurchase intention. These findings suggest that competitive pricing, effective promotional strategies, and a strong brand image are key determinants in fostering consumer loyalty and encouraging repeat purchases. Furthermore, this study highlights the importance for Mixue’s management to continuously evaluate and improve these factors in order to enhance consumer retention and sustain long-term business growth. The study provides practical implications for marketing strategy formulation in highly competitive markets, especially within the food and beverage industry. Additionally, future researchers are encouraged to include other variables such as product quality, customer satisfaction, and consumer trust to obtain a more comprehensive understanding of factors influencing repurchase intentions.